Answer:
we can get the figure EFGH from the figure ABCD by the following these steps.
Explanation:
1) to perform this it dilation, we just have to multiply the X & Y coordinates of the original shape by 2, like this ;
P (x, y)->P' (2x, 2y)
2) reflect
the new points over the x - axis
when we want to reflect a shape over the x - access we just have to invert the sign of the y - coordinate of its points, like this ;
P(x, y)-> P' (x, -y)
when we do this to the points that we got in the previous steps we get ;
A) '(0,0) ->E' (0,0)
B) '(0,4) -> F' (0,-4)
C) '(4,,2) -> C' (4,-2)
D) '(4,0) -> D' (4,0)
as you can see, the points that we got after these transactions correspond to the same points of the figure efgh know that the order in which you perform the transaction doesn't matter you could also have done the reflection and then the dilation.
the sequence of the transaction to get efgh from ABCD is ;
1) Diliate Abcd by a scale factor 2
2) reflect ABCD over the x - axis